Natural products: protective effects against ischemia-induced retinal injury - He, Qianxiong; Xiao, Liuyi; Shi, Yuanjiang; Li, Wanrong; Xin, Xiaorong (Frontiers in Pharmacology, 2023)
Ischemic retinal damage, a common condition associated with retinal vascular occlusion, glaucoma, diabetic retinopathy, and other eye diseases, threatens the vision of millions of people worldwide. It triggers excessive inflammation, oxidative stress, apoptosis, and vascular dysfunction, leading to the loss and death of retinal ganglion cells. Unfortunately, few drugs are available for treating eye diseases, and their efficacy and safety are limited. Therefore, there is an urgent need to develop more effective treatments for ischemic retinal damage. Natural compounds have been reported to have antioxidant, anti-inflammatory, and antiapoptotic properties that can be used to treat ischemic retinal damage. In addition, many natural compounds have been shown to exhibit biological functions and pharmacological properties relevant to the treatment of cellular and tissue damage. This article reviews the neuroprotective mechanisms of natural compounds in treating ischemic retinal injury. These natural compounds may serve as treatments for ischemia-induced ophthalmic diseases.